Haemophagocytic Lymphohistiocytosis in a Malay infant: Rare, Old and Often Forgotten Disease (Bangladesh Journal of Medical Science, 2022)
Haemophagocytic lymphohistiocytosis (HLH) is a rare disease but potentially life threatening clinical syndrome. It is caused by a multisystemic hyperinflammatory process secondary to severe hypercytokinemia with excessive and uncontrolled activation of the immune response. We report a case of familial HLH with no apparent causes in 6 months-old Malay girl presented with recurrent fever associated with severe anaemia and bleeding tendency requiring extensive treatment but refractory to the treatment which lead to mortality due to neutropenic sepsis indicating of poor prognosis of this disease. This familial type of HLH should be suspected in all children after excluding all the secondary causes with collective laboratory features and requiring extensive management as it associated with high mortality.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 196-200